(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article provides a comprehensive analysis of the geological structure, tectonic-structural features, and placement patterns of the gold mineralization of the Marjanbulak deposit, located in the Jizzakh region. The features of the morphology, size, vertical development, and mineralogical composition of ore bodies are highlighted. The presence of vertical zonality between oxidized and primary (elastic) ores is shown, and a geological and economic assessment of their development methods is provided. Based on revised geological data, the relationship between mineralization and a unified tectonically controlled zone has been substantiated, and practical recommendations have been developed for the development of exploration work and the expansion of the mineral resource base.